ChemInform Abstract: Reversible Deactivation Radical Polymerization Mediated by Cobalt Complexes: Recent Progress and Perspectives. Issue 52 (29th December 2014) - Peng, Chi‐How; Yang, Tsung‐Yao; Zhao, Yaguang; Fu, Xuefeng
Abstract Review: 68 refs.